The Japanese Canadians; Symbolic Politics In Action - Thompson, Ian James (My University, 1979)
In this thesis, the interaction between different participants is examined to determine how a particular political event was shaped . Canadian Japanese were discriminated against in an extremely severe fashion. In this thesis, the role of three major relationships is examined to determine the effect that they had on shaping end maintaining racial tensions. The three relationships are as follows; the relationship between the Japanese and their white competitors , the relationship between Canada and Japan, and the relationship between British Columbia and the rest of Canada. Using the work of Murray Edelman and Joseph Gusfield as a theoretical framework these three relationships are examined to see how they came to have effects far beyond their instrumental value.
Concern about the success of Japanese competition, fear of Japan's growing military power and anger a bout Canada's lack of concern about British Columbia's problems led to racial attacks and the eventual internment of the Japanese Canadian population.
Keywords: Political Science; Political Science